2008
DOI: 10.1002/ijc.24092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori infection on genetic instability, the aberrant CpG island methylation status and the cellular phenotype in Barrett's esophagus in a Japanese population

Abstract: Genetic or epigenetic alterations in Barrett's esophagus (BE) with/without Helicobacter pylori (H. pylori) infection remain unclear. We examined the effects of H. pylori infection on genetic instability (GIN), the CpG island methylation status and a biomarker related to BE carcinogenesis. We analyzed 113 Japanese individuals with endoscopically suspected BE. The patients included, Group CLE (n 5 25): no specialized intestinal metaplasia (SIM) in a columnar lined epithelium (control); Group BE (n 5 88): all had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 57 publications
3
20
0
1
Order By: Relevance
“…With regard to MSI, there have been several reports with similar findings, including our previous study, in which there was a positive association between MSI and BE or EAC, and in which MSI in BE was found to take place earlier in the development of SIM [29,32]. Thus, the genetic, as well as epigenetic, alterations present in EAC may already be present in BE [29,32].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…With regard to MSI, there have been several reports with similar findings, including our previous study, in which there was a positive association between MSI and BE or EAC, and in which MSI in BE was found to take place earlier in the development of SIM [29,32]. Thus, the genetic, as well as epigenetic, alterations present in EAC may already be present in BE [29,32].…”
Section: Discussionsupporting
confidence: 66%
“…Thus, the genetic, as well as epigenetic, alterations present in EAC may already be present in BE [29,32]. Although the incidence of molecular changes in SIM and CLE was slightly different from that found in our previous study [29], this might be accounted for by differences in the sample size and method of molecular analysis.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The association of the presence of H. pylori infection or the severity of gastric mucosal atrophy with the presence of ESEM was still controversial [41,44,45]. In general, many studies have shown that H. pylori infection and gastric mucosal atrophy are inversely associated with BE [25,46].…”
Section: Discussionmentioning
confidence: 99%